Assessing seniors’ satisfaction with local government activities in physical activity promotion: a comparative analysis - Sobczyk, Karolina; Łaskawiec-Żuławińska, Daria; Robakowska, Marlena; Krupa-Kotara, Karolina; Yanakieva, Antoniya; Grajek, Mateusz (Frontiers in Aging, 2024)
BackgroundThe aging population in Poland poses significant challenges to social and health systems. By 2050, the percentage of people over 65 in Poland is projected to reach 32.7%. Promoting physical activity among seniors is crucial for preventing chronic diseases, improving quality of life, and reducing healthcare burdens. Local governments play a pivotal role in implementing health-promoting measures.ObjectiveThe study aims to analyze seniors’ satisfaction with local government activities in promoting physical activity and to identify the best activities and future needs of seniors in the Silesia, Mazovia, and Pomerania regions of Poland.Material and MethodsThe survey, conducted between May 2023 and May 2024, utilized the Computer Assisted Web Interviewing (CAWI) method to gather data from 1,500 seniors aged 65 and above across the Silesia, Mazovia, and Pomerania regions. The study population was carefully selected to ensure representativeness in terms of gender, age, education, and place of residence. Data analysis included chi-square tests and logistic regression to assess satisfaction levels and identify influencing factors.ResultsThe survey revealed regional differences in satisfaction levels. Seniors in the Mazovia region exhibited the highest satisfaction (74% positive ratings), followed by the Silesian (64%) and Pomeranian (56%) regions. Factors influencing satisfaction included gender, age, education, and place of residence. Women, older seniors, those with higher education, and urban residents reported higher satisfaction levels. The most appreciated local government activities were related to sports infrastructure and sports programs. Future needs emphasized the demand for more sports programs and better infrastructure, with regional variations in preferences.ConclusionSeniors’ satisfaction with local government activities in promoting physical activity varies significantly across regions. Tailoring activities to regional preferences and continuous evaluation of programs are essential for enhancing effectiveness and satisfaction. Increased funding and support for physical activity programs are necessary, especially in less developed regions.